The Returns to Education in Africa: Some New Estimates - (:unkn) unknown (My University, 2014)
We estimate the rate of return to education for 12 African countries using recent data and a range of methodologies, which we apply consistently across all countries. Our findings confirm that the return to basic education is the lowest (7-10 per cent). The returns to upper secondary and tertiary education are similar to one another (25-30 per cent). Accounting for the risk of joblessness increases these rates of return, particularly for basic education and for women at tertiary level. Our results at the country level suggest that great care should be taken in choosing the appropriate methodology to estimate rates of return.
Keywords: African Research